The impact of an end-of-life healthcare ethics educational intervention. (March 2016) - Molloy, Claire; McCarthy, Joan; Tyrrell, Mark
Background: The impact of healthcare ethics educational interventions on participants' ethical development is rarely reported on and assessed; even less attention is paid to educational interventions that focus on end-of-life ethical issues. Aim: To evaluate the impact of the Ethical Framework for End-of-Life Care Study Sessions Programme ( EOLCSS ) on the moral development of healthcare staff who are delivering end-of-life care. Methods: The EOLCSS was delivered to 20 multi-disciplinary health care staff in Ireland in May 2013. Effect on moral reasoning was measured pre and post education using the Defining Issues Test 2 (DIT2). Inferential statistics were used to examine the relationships between change in DIT2 scores and demographic variables. Results: Participants experienced moral reasoning development following receipt of EOLCSS . Age and previous ethics education contributed to the observed changes in moral reasoning. Conclusions: Receipt of the EOLCSS may contribute to moral reasoning development in practicing healthcare professionals.